2004
DOI: 10.17159/2078-516x/2004/v16i1a189
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of satellite cells following ischaemia and reperfusion in primate skeletal muscle

Abstract: Objective. To describe the morphological and morphometric features of activated skeletal muscle satellite cells in primates, using an ischaemic reperfusion model. Setting. The study was undertaken at the Biomedical Resource Centre and the Electron Microscopy Unit of the University of KwaZulu-Natal. Interventions. Eight vervet monkeys were anaesthetised and subjected to 3 hours of tourniquet-induced lower limb ischaemia. Open muscle biopsies were taken from tibialis anterior muscle immediately after tourniquet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…Also activated satellite cells were observed with increased volume together with ribosomes in cytoplasm [41] . This finding was in agreement with other research [42] . Remarkably, it was reported that PRP produces a more pronounced increase of myogenic precursor cells together with an expansion of the myogenic cell pool necessary for myofiber formation [30] .…”
Section: Discussionsupporting
confidence: 94%
“…Also activated satellite cells were observed with increased volume together with ribosomes in cytoplasm [41] . This finding was in agreement with other research [42] . Remarkably, it was reported that PRP produces a more pronounced increase of myogenic precursor cells together with an expansion of the myogenic cell pool necessary for myofiber formation [30] .…”
Section: Discussionsupporting
confidence: 94%
“…Such activity prevents exit from the cell cycle which is required for cellular differentiation [41]. The process of myogenesis in adult ischaemic tissue may be incomplete as while satellite cells increase in number, these are generally not activated cells and cannot achieve maturity or differentiation [42]. Further work to elucidate the pathway that activates and causes the proliferation of quiescent satellite cells into myoblasts or renews the population of these active myogenic precursors would be the next logical step.…”
Section: Discussionmentioning
confidence: 99%
“…On the periphery of this severely damaged region (level 4) are myofibres that, whilst damaged, are still supplied with a limited blood supply. These myofibres may be repaired and remodelled by satellite cell or sarcolemmal fusion (Gregory & Mars 2004). The central region of the muscle is essentially cushioned from the crush component of the contusion and the vascular bed remains largely intact.…”
Section: Discussionmentioning
confidence: 99%